Dominasi Teknik Dasar pada Pencak Dor - Solihah, Rifa Atus; Yuliawan, Dhedhy; Firdaus , Mokhammad (MAN Insan Cendekia Jambi, 2024)
This study aims to analyse the dominant basic techniques used in Pencak Dor matches in Wates, Kediri, in 2024. This research utilises a quantitative descriptive method. This method focuses on the collection, analysis, and interpretation of numerical data to provide an objective and measurable description of a phenomenon or event. The results showed that the dominant technique used was a circular punch, with a total of 301 points with a percentage (45%) of a total of 50 warriors who climbed the bamboo ring. Analysing this technique is challenging because the movements in the match are fast, unpredictable, and performed at close range. To overcome this, researchers made observations through pencak dor videos uploaded on Youtube. These findings are expected to be the basis for developing strategies and coaching techniques in the sport of pencak dor in the future.